Laparoscopic ovariectomy in dogs in late gestation - Kaustubh R. Dongaonkar; Sarita U. Gulavane; Veeraraghavan M. Chariar; Kiran R. Shelar (BMC Veterinary Research, 2019)
Abstract Background Surgical sterilization of stray dogs is the most widely used technique to control stray dog population. Although ovariectomy is an effective technique for elective sterilization of female dogs, most stray dog population control programs generally utilize ovariohysterectomy for spaying female dogs. In the context of stray dog sterilization, laparoscopic ovariectomy has been utilized and reported to be cost-effective compared to programs utilizing open surgical approaches. However, when pregnant stray dogs are encountered either conventional ovariohysterectomy is performed or surgery is deferred altogether. It is reported that ovariectomy at any stage during canine pregnancy results in fetal resorption or abortion, however, clinical outcomes following laparoscopic ovariectomy in dogs in late gestation have not been previously reported. The purpose of this study was to investigate the outcome of laparoscopic ovariectomy with intra-gestational sac injection (IGSI) of potassium chloride (KCl) in dogs in late gestation. Results Eight client owned dogs in the gestational age range of 40–50 days underwent laparoscopic ovariectomy with IGSI of KCl. Laparoscopic ovariectomy resulted in decreased serum progesterone from 11.6 ± 2.6 ng/ml on day 0 to 1.3 ± 0.4 ng/ml 24 h’ post-surgery. IGSI of KCl did not result in immediate fetal death and fetal death temporally closely followed the drop in serum progesterone noted 24 h post-ovariectomy. Viscous brown vulvar discharge preceded fetal expulsion by 12 h and all the fetuses were dead when expelled. Uterine evacuation was documented within 45 ± 20 h (1–3.5 days) in all dogs without any clinically significant complications. Conclusion Laparoscopic ovariectomy enables elective termination of pregnancy and simultaneous neutering of dogs in late gestation and has potential applications in high volume stray dog sterilization programs which utilize laparoscopy. Utility of IGSI of KCl in this regard is unclear.